2014
DOI: 10.1016/j.ajps.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A quality by design (QbD) case study on enteric-coated pellets: Screening of critical variables and establishment of design space at laboratory scale

Abstract: PlacketteBurman designBoxeBehnken design Naproxen Quality by design a b s t r a c tThe study aims to prepare naproxen enteric-coated pellets (NAP-ECPs) by fluid-bed coating using QbD principle. Risk assessment was firstly performed by using failure mode and effect analysis (FMEA) methodology. A PlacketteBurman design was then used for assessment of the most important variables affecting enteric-coated pellets characteristics. A BoxeBehnken design was subsequently used for investigating the main, interactive, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 19 publications
0
21
0
2
Order By: Relevance
“…Therefore, the QbD approach is more proactive and refers to a systematic process compared to the mainly empirical methodologies used earlier (Beg, S. et al, 2015, Shah, B. et al, 2015, Xu, X. et al, 2011Xu, X. et al, 2012, Kan, S. et al, 2014, Wang, J. et al, 2015, Kovacs, A et al, 2016. Risk assessment and the Design of Experiments (DoE) techniques within the risk assessment process are key elements of QbD methodology (Fig.1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the QbD approach is more proactive and refers to a systematic process compared to the mainly empirical methodologies used earlier (Beg, S. et al, 2015, Shah, B. et al, 2015, Xu, X. et al, 2011Xu, X. et al, 2012, Kan, S. et al, 2014, Wang, J. et al, 2015, Kovacs, A et al, 2016. Risk assessment and the Design of Experiments (DoE) techniques within the risk assessment process are key elements of QbD methodology (Fig.1).…”
Section: Introductionmentioning
confidence: 99%
“…Acid resistance and cumulative drug release were identified CQAs, based on which design space was established. Confirmation tests showed that the predicted and the response values of the formulations with different variables were similar, thus the validity of the model was established and all the parameters were robust within design space 10 . Coating Process Optimization: Variability in the coating thickness is a common problem during tablet coating; it alters the aesthetics and taste masking properties.…”
Section: Quality By Design In Formulationmentioning
confidence: 89%
“…(3) identifying, through prior knowledge, experimentation, and risk assessment, the material attributes and process parameters that can have an effect on product CQAs; (4) determining the functional relationships that link material attributes and process parameters to product CQAs through the development of multivariate experiments using Design of Experiments (DoE); (5) establishing a design space, and (6) ensuring continual improvement and innovation throughout the product lifecycle [19,23].…”
Section: Introductionmentioning
confidence: 99%